P‐114: Non‐Doped White Light‐Emitting Electrochemical Cells Employing Plasmonic Notch Filters. Issue 1 (May 2017) - Lee, Hsiao-Chin; Lin, Chia-Ching; Yao, Yung-Chi; Sarma, Monima; Su, Hai-Ching; Yang, Zu-Po; Lee, Ya-Ju; Wong, Ken-Tsung
Abstract : White light‐emitting electrochemical cells employing integrated plasmonic notch filter to tailor the electroluminescence spectrum of non‐doped blue‐green emissive material are demonstrated. The plasmonic notch filter is composed of randomly distributed silver nanoparticles embedded in the indium‐tin‐oxide anode contact, which is compatible with well developed technologies used in light‐emitting diode industry.